Prognostic impact of the loss of E-cadherin and de novo expression of N-cadherin at the invasive front of primary and recurrent oral squamous cell carcinoma - Hakim, Samer George; Taubitz, Clara; Hoppe, Steffen; Steller, Daniel; Rades, Dirk; Ribbat-Idel, Julika; Alsharif, Ubai; Falougy, Mohamed (Frontiers in Oncology, 2023)
The epithelial-mesenchymal transition (EMT) is a biological mechanism in multiple pathophysiological diseases. Related alterations in cadherin expression play a crucial role in carcinogenesis, progression, angiogenesis, and immune response. EMT cells exhibit a transition from an epithelial to a mesenchymal phenotype (cadherin-switch). This process is characterized by the de novo development of N-cadherin (N-CAD), which replaces E-cadherin (E-CAD) and signifies an increased migratory capacity and malignant transformation. The cadherin switch is a hallmark of EMT and has been studied in various cancer entities. We predicted that the cadherin switch in the primary and recurrent oral squamous cell carcinoma (re-OSCC) tissues is an inherent characteristic of the tumor, affects the biologic behavior, and further reflects the post-recurrence survival outcome of these patients. Survival outcome was analyzed by calculating the post-recurrence survival of the high-risk group and correlating the standardized h-score-based IHC expression of both cadherin types with the clinical follow-up. 94 patients with re-OSCC were observed within the cohort. Tissue samples from both primary and recurring tumors were collected. There was a significant association between loss of E-CAD expression and both oral cancer-specific and overall survival, (HR=2.72, CI:1.50-4.95, p=0.001) and (HR=3.84, CI:1.93-7.63, p=0.001), respectively, for expression loss higher than 60%. There was no statistically significant correlation between N-CAD de novo expression and Overall, oral cancer-specific and disease-free post-recurrence survival. The current study clearly shows that cadherin-switch, identified as E-CAD loss and N-CAD de novo expression in the invasion front of a re-OSCC, appears to be an inherent histological hallmark that does not change from primary manifestation to recurrence within the same tumor, regardless of the form of adjuvant therapy used for the primary tumor. The loss of E-CAD expression in re-OSCC is an independent risk factor for poor survival, and may be used to stratify therapy and de/escalate the multimodal treatment.